2018
DOI: 10.1186/s12955-018-0951-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome measures used in patients with primary sclerosing cholangitis: a systematic review

Abstract: BackgroundPrimary Sclerosing Cholangitis (PSC) is a rare chronic, cholestatic liver condition in which patients can experience a range of debilitating symptoms. Patient reported outcome measures (PROMs) could provide a valuable insight into the impact of PSC on patient quality of life and symptoms. A previous review has been conducted on the quality of life instruments used in liver transplant recipients. However, there has been no comprehensive review evaluating PROM use or measurement properties in PSC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 67 publications
(71 reference statements)
0
20
0
Order By: Relevance
“…Although the CLDQ has been reported to have good test-retest reliability and cross-sectional validity, [52] this should be interpreted with caution as the evidence was obtained from studies that combined the results of patients with PSC with that of patients with primary biliary cirrhosis (PBC) and hepatitis B & C [53,54]. Preliminary validation of the PSC PRO, a new measure developed in accordance with FDA guidelines suggests good psychometric properties [55,56]. The PedsQL-TM has been reported to have good reliability and validity in young patients with transplant [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the CLDQ has been reported to have good test-retest reliability and cross-sectional validity, [52] this should be interpreted with caution as the evidence was obtained from studies that combined the results of patients with PSC with that of patients with primary biliary cirrhosis (PBC) and hepatitis B & C [53,54]. Preliminary validation of the PSC PRO, a new measure developed in accordance with FDA guidelines suggests good psychometric properties [55,56]. The PedsQL-TM has been reported to have good reliability and validity in young patients with transplant [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The review found that a wide diversity of PROMs were used to measure HRQoL and symptom burden in patients with PSC. However, the quality of the evidence to support reliability and validity in the most commonly used measures was generally poor and only one had been validated within this population following FDA guidelines [ 70 , 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was therefore a lack of clarity about how QoL had been measured in this population, which factors were important determinants of QoL in PSC, and how the condition affected QoL. Four more reviews by other groups have since been published, and were identified in later updates to the initial search: a systematic review assessing PROMs used in PSC [ 22 ], a systematic review identifying PRO instruments and concepts used in the PSC literature [ 23 ], a literature review exploring QoL in cholestatic disease [ 24 ], and a scoping review exploring the impact of PSC on psychological well-being [ 25 ].…”
Section: Introductionmentioning
confidence: 99%